A positive electrode-solid electrolyte integrated material and its preparation method and application
By using the positive-solid electrolyte integrated materials in lithium ion batteries, and using PTCDA and other materials to improve the ion conductivity and interface contact of solid electrolytes, solve the problem of poor flammable electrolyte and interface contact in conventional lithium ion batteries. Higher cycle performance and voltage window.
Patent Information
- Application Number
- CN202411223155.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The electrolyte in conventional lithium-ion batteries is flammable, and the interface contact between the solid electrolyte and other battery materials is poor, resulting in low ionic conductivity and hindering the development of solid electrolytes.
The positive electrode-solid electrolyte integrated material is used, including a solid electrolyte layer and a positive electrode layer. The solid electrolyte layer is composed of lithium salt, PTCDA and polymer, and the positive electrode layer is composed of activated PTCDA, carbon source and polymer. The integrated material is obtained through pressing and assembly.
By increasing the internal lithium ion transmission channel, improve the ion conductivity of solid electrolytes, enhance the interface contact between the positive polar layer and the solid electrolyte layer, reduce the interface transmission, load impedance, and improve the cycle performance and voltage window of the battery.
Smart Images

Figure CN118763293B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion battery materials and relates to a solid electrolyte, in particular to a positive electrode-solid electrolyte integrated material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in mobile devices, electric vehicles, energy storage systems, aerospace and other fields due to their high energy density and long cycle life. However, the electrolyte in conventional lithium-ion batteries is a flammable organic solvent with high saturated vapor pressure. When thermal runaway occurs, it is often accompanied by combustion of electrolyte vapor or even explosion of the battery.
[0003] In order to reduce the combustion characteristics of the electrolyte, the use of solid materials as electrolytes can greatly improve the flame retardancy and high temperature stability of the battery. Solid electrolytes have high mechanical strength and cannot penetrate deep into other battery materials, resulting in poor interface contact between solid electrolytes and other battery materials, and most contacts are point contacts. In addition, since solid electrolytes have almost no fluidity and low ionic conductivity, the development of solid electrolytes is hindered. Overcoming the above problems of solid electrolytes is conducive to the development of solid electrolytes. Summary of the invention
[0004] In view of the above problems existing in the prior art, in the first aspect, the present invention provides a positive electrode-solid electrolyte integrated material; in the second aspect, the present invention provides a method for preparing the above positive electrode-solid electrolyte integrated material; in the third aspect, the present invention provides an application of the above positive electrode-solid electrolyte integrated material.
[0005] In a first aspect, a positive electrode-solid electrolyte integrated material includes a solid electrolyte layer and a positive electrode layer, wherein the solid electrolyte layer includes a lithium salt, PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride), and a polymer; and the positive electrode layer includes activated PTCDA, a carbon source, and a polymer.
[0006] In a second aspect, the present invention provides a method for preparing a positive electrode-solid electrolyte integrated material, comprising the following steps:
[0007] Preparing a solid electrolyte layer: adding lithium salt, PTCDA, and polymer into a first solvent to obtain slurry A; coating slurry A on a substrate, and drying to obtain a solid electrolyte layer;
[0008] Preparation of the positive electrode layer: activating PTCDA at high temperature in an inert atmosphere to obtain activated PTCDA; adding the activated PTCDA, a carbon source, and a polymer into a second solvent to obtain slurry B; coating the slurry B on a substrate, and drying to obtain a positive electrode layer;
[0009] Assembly: Press the solid electrolyte layer and the positive electrode layer to obtain a positive electrode-solid electrolyte integrated material.
[0010] Preferably, in slurry A, the lithium salt is LiFSI, LiPF 6 、LiNO 3 Any one or two or more of the following.
[0011] Preferably, in slurry A, the polymer is one or more of PVDF, PVDF-HFP and PVDF-CTFE.
[0012] Preferably, in slurry A, the first solvent is one or both of DMF and THF.
[0013] More preferably, in slurry A, the concentration of lithium salt is 30-80 g / L.
[0014] More preferably, in slurry A, the concentration of PTCDA is 1.6-11.2 g / L.
[0015] More preferably, in slurry A, the concentration of the polymer is 80 to 140 g / L.
[0016] Preferably, when drying the solid electrolyte layer, it is dried at room temperature for 12 to 24 hours and then dried at 90 to 100° C. for 1 to 2 hours.
[0017] Preferably, the activation of PTCDA includes a heating stage and a constant temperature stage; the heating rate is 5-10°C / min; the constant temperature is 400-480°C; and the constant temperature time is 3-6h.
[0018] Preferably, when PTCDA is activated, the gas providing the inert atmosphere is one or both of argon and nitrogen.
[0019] Preferably, in slurry B, the carbon source is one or both of acetylene black and Super P.
[0020] Preferably, in slurry B, the polymer is PVDF.
[0021] Preferably, in slurry B, the second solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide.
[0022] Preferably, in slurry B, the mass ratio of activated PTCDA, carbon source and polymer is 8-28:1:1.
[0023] Preferably, in slurry B, the solid-to-liquid ratio of the mixture of activated PTCDA, carbon source, polymer and the second solvent is 0.1-0.25.
[0024] Preferably, the drying temperature of the positive electrode layer is 90-100° C. and the drying time is 2-4 hours.
[0025] Preferably, during coating, the substrate is any one of a glass plate, a Teflon plate, and an aluminum foil.
[0026] Preferably, during coating, the scraper used has a thickness of 400-600 μm.
[0027] Preferably, during assembly, the pressing pressure is 10-25 N / cm 2 The pressing time is 2~6h.
[0028] In a third aspect, the present invention provides a lithium battery comprising the above-mentioned positive electrode-solid electrolyte integrated material.
[0029] Compared with the prior art, the present invention has the following obvious beneficial technical effects:
[0030] (1) By adding PTCDA to the solid electrolyte layer and the positive electrode layer, the lithium ion transmission channels and sites inside the material are increased, and the ionic conductivity of the solid electrolyte is improved. In addition, the PTCDA in the solid electrolyte layer and the activated PTCDA in the positive electrode layer have similar molecular structures, which can increase the interface contact between the positive electrode layer and the solid electrolyte layer and reduce the interface mass transfer and charge transfer impedance.
[0031] (2) The preparation method of the positive electrode-solid electrolyte integrated material provided by the present invention is simple, low in energy consumption, low in cost, easy to promote and industrialize, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The cycle performance diagrams are the cycle performance diagrams of batteries assembled from the positive electrode-solid electrolyte integrated materials prepared in Example 1 and Comparative Examples 1-2.
[0033] Figure 2 The cycle performance diagram of the battery assembled from the positive electrode-solid electrolyte integrated material prepared in Examples 2 to 3, the solid electrolyte prepared in Comparative Example 3, and the positive electrode material prepared in Comparative Example 4.
[0034] Figure 3 This is a voltage window test diagram of a battery assembled with the positive electrode-solid electrolyte integrated materials prepared in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0035] The present invention provides the following specific technical solutions.
[0036] In a first aspect, a positive electrode-solid electrolyte integrated material includes a solid electrolyte layer and a positive electrode layer, wherein the solid electrolyte layer includes a lithium salt, PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride), and a polymer; and the positive electrode layer includes activated PTCDA, a carbon source, and a polymer.
[0037] The inventors have found through research that when preparing solid electrolytes, organic materials are used to prepare the positive electrode layer, and traditional positive electrode materials based on transition metals are not used, which reduces environmental pollution caused by heavy metals and reduces the cost problems caused by transition metals. PTCDA is a kind of energy storage material. During the high-temperature activation process, the oxygen functional groups between different molecules will combine to form a three-dimensional network microstructure. In addition, since the rich oxygen functional groups can bind lithium, the energy storage performance is excellent. Adding activated PTCDA to the positive electrode layer, on the one hand, reduces the crystallinity of the polymer molecules and increases the intrinsic ion conductivity; on the other hand, PTCDA also has multiple lithium contact sites to increase ion conductivity. In addition, the PTCDA in the solid electrolyte layer and the activated PTCDA in the positive electrode layer have similar molecular structures, which can increase the interface contact between the positive electrode layer and the solid electrolyte layer and reduce the interface mass transfer and charge transfer impedance.
[0038] In a second aspect, the present invention provides a method for preparing a positive electrode-solid electrolyte integrated material, comprising the following steps:
[0039] Prepare a solid electrolyte layer: add lithium salt, PTCDA, and polymer into a first solvent, and stir to obtain slurry A; apply slurry A on a substrate, and dry to obtain a solid electrolyte layer;
[0040] Preparation of the positive electrode layer: activating PTCDA at high temperature in an inert atmosphere to obtain activated PTCDA; adding the activated PTCDA, the carbon source, and the polymer into the second solvent, stirring and adding to obtain slurry B; coating the slurry B on the substrate, and drying to obtain the positive electrode layer;
[0041] Assembly: After pressing the solid electrolyte layer and the positive electrode layer for a certain period of time, the positive electrode-solid electrolyte integrated material is obtained.
[0042] Preferably, in slurry A, the lithium salt is LiFSI (lithium bis(fluorosulfonyl)imide) or LiPF 6 (Lithium hexafluorophosphate), LiNO 3 (lithium nitrate).
[0043] Preferably, in slurry A, the polymer is one or more of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-trifluoroethylene-2-acryloyl polycaprolactone), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene copolymer).
[0044] Preferably, in slurry A, the first solvent is one or both of DMF (N,N-dimethylformamide) and THF (tetrahydrofuran).
[0045] More preferably, the concentration of lithium salt in slurry A is 30-80 g / L.
[0046] More preferably, in slurry A, the concentration of PTCDA is 1.6-11.2 g / L.
[0047] More preferably, in slurry A, the concentration of the polymer is 80 to 140 g / L.
[0048] In practical applications, the addition amounts of lithium salt, PTCDA and polymer in slurry A can be selected according to actual needs. The concentrations of lithium salt in slurry A obtained by the inventors through multiple experiments are 30-80 g / L, 1.6-11.2 g / L and 80-140 g / L, which are only preferred ranges.
[0049] Preferably, when drying the solid electrolyte layer, it is dried at room temperature for 12 to 24 hours and then dried at 90 to 100° C. for 1 to 2 hours.
[0050] In practical applications, the room temperature drying time, drying temperature and drying time of the solid electrolyte layer can be adjusted according to actual conditions. In a specific embodiment of the present invention, the room temperature drying time can be 12h, 18h, or 24h; the drying temperature can be 90°C, 95°C, or 100°C; and the drying time can be 1h, 1.5h, or 2h.
[0051] Preferably, the activation of PTCDA includes a heating stage and a constant temperature stage; the heating rate is 5-10°C / min; the constant temperature is 400-480°C; and the constant temperature time is 3-6h.
[0052] The inventors have found through research that the activation temperature of PTCDA is preferably 400-480°C. If the activation temperature is too high, the degree of carbonization will be too high, resulting in excessive mass loss and the structure will be destroyed; if the activation temperature is too low, it will be unfavorable for cross-linking between molecules.
[0053] The heating rate, constant temperature and constant time during PTCDA activation can be adjusted according to actual conditions. In a specific embodiment of the present invention, the heating rate can be 5°C / min, 8°C / min, or 10°C / min; the constant temperature can be 400°C, 440°C, or 480°C; and the constant time can be 3h, 5h, or 6h.
[0054] Preferably, when PTCDA is activated, the gas providing the inert atmosphere is one or both of argon and nitrogen.
[0055] Preferably, in slurry B, the carbon source is one or both of acetylene black and Super P.
[0056] Preferably, in slurry B, the polymer is PVDF.
[0057] Preferably, in slurry B, the second solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide.
[0058] Preferably, in slurry B, the mass ratio of activated PTCDA, carbon source and polymer is 8-28:1:1.
[0059] Preferably, in slurry B, the solid-to-liquid ratio of the mixture of activated PTCDA, carbon source, polymer and the second solvent is 0.1-0.25.
[0060] In practical applications, the amount of the second solvent added can be adjusted according to actual conditions, and the added second solvent can be adjusted to make the mixed material viscous.
[0061] Preferably, the drying temperature of the positive electrode layer is 90-100° C. and the drying time is 2-4 hours.
[0062] Preferably, during coating, the substrate is any one of a glass plate, a Teflon plate, and an aluminum foil.
[0063] Preferably, during coating, the scraper used has a thickness of 400-600 μm.
[0064] Preferably, during assembly, the pressing pressure is 10-25 N / cm 2 The pressing time is 2~6h.
[0065] In practical applications, the pressing pressure and pressing time can be adjusted according to actual conditions. In a specific embodiment of the present invention, the pressing pressure can be 10N / cm 2 , 15N / cm 2 , 25N / cm 2 ; The pressing time can be 2h, 4h, or 6h.
[0066] In a third aspect, the present invention provides a lithium battery comprising the above-mentioned positive electrode-solid electrolyte integrated material.
[0067] In order to make the technical problems to be solved, technical solutions and technical advantages of the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.
[0068] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0069] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0070] Embodiment 1:
[0071] A solid composite electrolyte comprises the following steps:
[0072] Step 1, take 5gLiFSI, 0.4gPTCDA, and 11gPVDF-HFP and add them to 100mlDMF, stir them thoroughly to obtain slurry A, use a 500μm scraper to scrape part of the slurry A on a glass plate with a scraping thickness of 500μm, then let the glass plate stand and dry at room temperature for 18h, then transfer it to a 95℃ forced air oven and dry it for 1.5h to obtain a solid electrolyte layer;
[0073] Step 2: In an argon atmosphere, PTCDA is heated to 440° C. at a heating rate of 8° C. / min, then kept at this temperature for 5 h, and then cooled to room temperature to obtain activated PTCDA.
[0074] Step 3, add 18g activated PTCDA, 1g acetylene black, and 1g polyvinylidene fluoride into 100g N-methylpyrrolidone, stir evenly to obtain slurry B, take part of slurry B and evenly coat it on aluminum foil (aluminum foil thickness 12μm), the coating thickness is 200μm, and obtain the positive electrode layer after drying.
[0075] Step 4: The solid electrolyte layer and the cathode layer are heated to 15 N / cm 2 After bonding under pressure for 4 hours, the positive electrode-solid electrolyte integrated material is obtained.
[0076] Embodiment 2:
[0077] A solid composite electrolyte comprises the following steps:
[0078] Step 1, take 3gLiPF 6 , 0.16g PTCDA, and 8g PVDF were added to 100ml DMF, and the mixture was stirred thoroughly to obtain slurry A. A portion of the slurry A was scraped onto a Teflon plate using a 400μm scraper to a thickness of 500μm. The glass plate was then placed to dry at room temperature and then transferred to a 90℃ forced air oven for drying for 1h to obtain a solid electrolyte layer.
[0079] Step 2: PTCDA is heated to 400° C. at a heating rate of 5° C. / min under an argon atmosphere, then kept at this temperature for 3 h, and then cooled to room temperature to obtain activated PTCDA.
[0080] Add 8 g activated PTCDA, 1 g Super P and 1 g PVDF into 100 ml N,N-dimethylformamide and stir evenly to obtain slurry B. Take part of slurry B and evenly coat it on a glass plate with a coating thickness of 200 μm. After drying, obtain a positive electrode layer.
[0081] Step 3: The solid electrolyte layer and the cathode layer are heated to 10 N / cm2 After bonding under pressure for 2 hours, the positive electrode-solid electrolyte integrated material is obtained.
[0082] Embodiment 3:
[0083] A solid composite electrolyte comprises the following steps:
[0084] Step 1, take 8g LiNO 3 , 1.12g PTCDA, 14g PVDF-CTFE were added to 100ml DMF, and the mixture was stirred thoroughly to obtain slurry A. A portion of slurry A was scraped onto a Teflon plate using a 600μm scraper to a thickness of 500μm. The slurry was allowed to stand and dry at room temperature for 24h, and then dried in a 100℃ forced air oven for 2h to obtain a solid electrolyte layer.
[0085] Step 2: In an argon atmosphere, PTCDA is heated to 480° C. at a heating rate of 10° C. / min, then kept at this temperature for 6 hours, and then cooled to room temperature to obtain activated PTCDA.
[0086] 18 g of activated PTCDA, 1 g of acetylene black and 1 g of polyvinylidene fluoride were added to 80 ml of N,N-dimethylformamide, stirred evenly, and coated evenly on a glass plate with a coating thickness of 200 μm. After drying, a positive electrode layer was obtained.
[0087] Step 3: The solid electrolyte layer and the cathode layer are heated to 25 N / cm 2 After bonding under pressure for 6 hours, the positive electrode-solid electrolyte integrated material is obtained.
[0088] Comparative Example 1:
[0089] The difference from Example 1 is that in step 1, PTCDA is not added.
[0090] Comparative Example 2:
[0091] The difference from Example 2 is that in step 2, PTCDA is not activated.
[0092] Comparative Example 3:
[0093] A solid electrolyte comprises the following steps:
[0094] Take 8gLiNO 3 , 1.12gPTCDA and 14gPVDF-CTFE were added to 100mlDMF and stirred thoroughly to obtain slurry A. Part of the slurry A was scraped onto a Teflon plate using a 600μm scraper with a coating thickness of 500μm. The plate was allowed to stand and dry at room temperature for 24h, and then dried in a 100℃ forced air oven for 2h to obtain a solid electrolyte.
[0095] Comparative Example 4:
[0096] PTCDA was heated to 440°C at a heating rate of 8°C / min under an argon atmosphere, then kept at that temperature for 5 hours and cooled to room temperature to obtain activated PTCDA.
[0097] Add 18g activated PTCDA, 1g acetylene black and 1g polyvinylidene fluoride into 100ml N-methylpyrrolidone and stir evenly to obtain slurry B. Take part of slurry B and evenly coat it on aluminum foil (aluminum foil thickness 12μm) with a coating thickness of 200μm. After drying, a positive electrode is obtained.
[0098] The solid electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were cut into discs with a diameter of 16 mm to serve as solid electrolytes and positive electrodes, and the lithium sheets with a thickness of 100 μm were cut into discs with a diameter of 12 mm to serve as negative electrodes. They were placed in a glove box filled with argon atmosphere with a water content and an oxygen content both lower than 0.01 ppm for 4 hours to reduce the moisture adsorbed by all materials during the transfer process, and then assembled into CR2032 button batteries in the glove box.
[0099] The solid electrolyte prepared in Comparative Example 3 was cut into discs with a diameter of 16 mm; a lithium sheet with a thickness of 100 μm was cut into discs with a diameter of 12 mm as the negative electrode; a commercial six-series (622) ternary positive electrode material was mixed with a conductive agent acetylene black (AB) and a binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a small beaker and stirred at a speed of 800 r / min for 2 hours to obtain a slurry. The slurry was coated on the current collector aluminum foil by a dynamic coater, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4 hours, punched into a positive electrode sheet with a diameter of 12 mm, and then dried at 105°C in a vacuum drying oven for 4 hours. The sheet was placed in a glove box filled with argon atmosphere with a water content and oxygen content both lower than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the sheet during the transfer process, and then the solid electrolyte, negative electrode sheet and positive electrode sheet were assembled into a CR2032 button battery in the glove box.
[0100] The positive electrode material prepared in Comparative Example 4, the conductive agent acetylene black (AB), and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The mixture was placed in a small beaker and stirred at a speed of 800r / min for 2h to obtain a slurry. The slurry was coated on the current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for 4h. After punching into a positive electrode sheet with a diameter of 12mm, it was dried at 105°C in a vacuum drying oven for 4h, and placed in a glove box filled with argon atmosphere with a water content and oxygen content of less than 0.01ppm for 4h to reduce the moisture adsorbed by the electrode during the transfer process. A lithium sheet with a thickness of 100μm was cut into a disc with a diameter of 12mm to serve as the negative electrode. Take 8gLiNO 3 , 14g PVDF-CTFE were added into 100ml DMF and stirred thoroughly to obtain slurry A. Part of slurry A was scraped onto a Teflon plate using a 600μm scraper to a thickness of 500μm. The slurry was allowed to dry at room temperature for 24h, and then dried in a 100℃ forced air oven for 2h to obtain a solid electrolyte. The solid electrolyte was cut into discs with a diameter of 16mm, and then the solid electrolyte, negative electrode sheet and positive electrode sheet were assembled into a CR2032 button battery in a glove box.
[0101] After the battery was assembled and aged for 12 hours, the charge and discharge tests were performed at different potentials. The discharge specific capacity of the sample after 200 cycles at a voltage of 1.5-3.5V and a current density of 0.5C at room temperature is shown in Table 1 below.
[0102] Table 1 - Discharge capacity of batteries assembled from materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 (unit: mAh / g)
[0103]
[0104] Figure 1 The cycle performance diagram of the battery assembled from the positive electrode-solid electrolyte integrated materials prepared in Example 1 and Comparative Examples 1-2; Figure 2 The cycle performance diagram of the battery assembled from the positive electrode-solid electrolyte integrated material prepared in Examples 2 to 3, the solid electrolyte prepared in Comparative Example 3, and the positive electrode material prepared in Comparative Example 4. Figure 1 and Figure 2 It can be seen that the battery assembled with the composite solid electrolytes prepared in Examples 1 to 3 was cycled 200 times, and its discharge specific capacity was almost a horizontal straight line, which can to some extent illustrate that the composite solid electrolyte provided by the present invention has excellent cycle stability.
[0105] The cycle performance of the battery assembled with the composite solid electrolyte prepared in Example 1 is higher than that of the battery assembled with the composite solid electrolyte prepared in Comparative Example 1, indicating that adding PTCDA to the solid electrolyte can improve the cycle performance of the battery.
[0106] The cycle performance of the battery assembled with the composite solid electrolyte prepared in Example 1 is higher than that of the battery assembled with the composite solid electrolyte prepared in Comparative Example 2, indicating that the positive electrode layer prepared with activated PTCDA can improve the cycle performance of the battery.
[0107] By comparing the battery assembled with the composite solid electrolyte prepared in Example 1, the battery assembled with the solid electrolyte prepared in Example 3, and the battery assembled with the positive electrode prepared in Example 4, it can be seen that the solid electrolyte layer combined with the positive electrode layer provided by the present invention makes the battery cycle performance more excellent.
[0108] From the discharge specific capacities of the battery assembled from the solid electrolyte prepared in Comparative Example 3 and the battery assembled from the positive electrode prepared in Comparative Example 4, it can be seen that the solid electrolyte and the activated positive electrode provided by the present invention cooperate with each other.
[0109] The conductivity test was performed on the batteries assembled from the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4. The test method is as follows:
[0110] The EIS impedance spectroscopy test of the electrochemical workstation was carried out in the range of 1~100000 Hz, and the Rs value was obtained by fitting. The calculation formula of the ionic conductivity is: σ=L / RS, where L is thickness, R is resistance, and S is area.
[0111] The calculated ionic conductivities of Examples 1 to 3 and Comparative Examples 1 to 4 were 5.2×10 -4 S / cm, 4.9×10 -4 S / cm, 4.8×10 -4 S / cm, 2.0×10 -4 S / cm, 1.3×10 -4 S / cm, 1.5×10 -4 S / cm, 1.4×10 -4 S / cm.
[0112] It can be seen that the ionic conductivity performance of the solid electrolytes prepared in Examples 1 to 3 is more excellent.
[0113] The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were used as raw materials to assemble batteries and then subjected to cyclic voltammetry testing at a scan rate of 1.0 mV / s. The test data are as follows:
[0114] Table 2 - High voltage windows of batteries assembled using the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 as raw materials
[0115]
[0116] Figure 3 The voltage window test diagram of the battery assembled with the positive electrode-solid electrolyte integrated material prepared in Example 1 and Comparative Examples 1-2 is shown in Table 2 and Figure 3 It can be seen that the positive electrode-solid electrolyte integrated material provided by the present invention combines the positive electrode material with the solid electrolyte, so that the interface state is well modified and the interface stability is increased. At the same time, it can also show a good phenomenon of inhibiting side reactions under high voltage, thereby broadening the voltage window of the battery.
[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode-solid electrolyte integrated material, characterized in that: The steps include: Preparing a solid electrolyte layer: adding lithium salt, PTCDA, and polymer into a first solvent to obtain slurry A; coating slurry A on a substrate, and drying to obtain a solid electrolyte layer; Preparation of the positive electrode layer: activating PTCDA at high temperature in an inert atmosphere to obtain activated PTCDA; adding the activated PTCDA, a carbon source, and a polymer into a second solvent to obtain slurry B; coating the slurry B on a substrate, and drying to obtain a positive electrode layer; Assembly: Pressing the solid electrolyte layer and the cathode layer to obtain the cathode-solid electrolyte integrated material; In slurry A, the polymer is one or more of PVDF, PVDF-HFP, and PVDF-CTFE; In slurry B, the polymer is PVDF; the carbon source is one or two of acetylene black and Super P; When PTCDA is activated, it includes a heating stage and a constant temperature stage; the heating rate is 5~10℃ / min; The constant temperature is 400~480℃; the constant temperature time is 3~6h.
2. The method for preparing the cathode-solid electrolyte integrated material according to claim 1, characterized in that: The lithium salt is any one or more of LiFSI, LiPF6, and LiNO3; the first solvent is one or two of DMF and THF.
3. The method for preparing the cathode-solid electrolyte integrated material according to claim 1 or 2, characterized in that: In slurry A, the concentration of lithium salt is 30~80g / L; the concentration of PTCDA is 1.6~11.2g / L; and the concentration of polymer is 80~140g / L.
4. The method for preparing the cathode-solid electrolyte integrated material according to claim 1, characterized in that: When drying the solid electrolyte layer, dry it at room temperature for 12 to 24 hours, and then dry it at 90 to 100°C for 1 to 2 hours.
5. The method for preparing the cathode-solid electrolyte integrated material according to claim 1 or 4, characterized in that: The second solvent is one or both of N-methylpyrrolidone and N,N-dimethylformamide.
6. The method for preparing the cathode-solid electrolyte integrated material according to claim 1, characterized in that: In slurry B, the mass ratio of activated PTCDA, carbon source and polymer is 8-28:1:1; the solid-liquid ratio of the mixture of activated PTCDA, carbon source and polymer and the second solvent is 0.1-0.
25.
7. The method for preparing the cathode-solid electrolyte integrated material according to claim 1, characterized in that: The drying temperature of the positive electrode layer is 90~100°C; the drying time is 2~4h.
8. A positive electrode-solid electrolyte integrated material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7.
9. A lithium battery, characterized in that: Comprising the positive electrode-solid electrolyte integrated material as described in claim 8.
Citation Information
Patent Citations
Polyimide composite carbon aerogel lithium battery positive electrode slurry, positive electrode plate and preparation method of positive electrode plate
CN116706009A
Lithium ion battery solid electrolyte with positive and negative electrode interface modification and preparation method of lithium ion battery solid electrolyte
CN118412528A